2019
DOI: 10.1371/journal.pbio.3000059
|View full text |Cite
|
Sign up to set email alerts
|

Adding function to the genome of African Salmonella Typhimurium ST313 strain D23580

Abstract: Salmonella Typhimurium sequence type (ST) 313 causes invasive nontyphoidal Salmonella (iNTS) disease in sub-Saharan Africa, targeting susceptible HIV+, malarial, or malnourished individuals. An in-depth genomic comparison between the ST313 isolate D23580 and the well-characterized ST19 isolate 4/74 that causes gastroenteritis across the globe revealed extensive synteny. To understand how the 856 nucleotide variations generated phenotypic differences, we devised a large-scale experimental approach that involved… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
165
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(171 citation statements)
references
References 90 publications
(154 reference statements)
3
165
0
Order By: Relevance
“…A comparison of the coding sequences (CDS) of the enzymes involved in the riboflavin biosynthesis pathway found only one nucleotide change (SNP) between the sequence type 19 STM-4/74 and the sequence type 313 STM-D23580 strains. This synonymous coding variant was located in the ribD gene (Glu316Glu) [43], suggesting that there were no biochemical differences between the riboflavin biosynthesis pathways of the sequence type 313 and sequence type 19 isolates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A comparison of the coding sequences (CDS) of the enzymes involved in the riboflavin biosynthesis pathway found only one nucleotide change (SNP) between the sequence type 19 STM-4/74 and the sequence type 313 STM-D23580 strains. This synonymous coding variant was located in the ribD gene (Glu316Glu) [43], suggesting that there were no biochemical differences between the riboflavin biosynthesis pathways of the sequence type 313 and sequence type 19 isolates.…”
Section: Resultsmentioning
confidence: 99%
“…Data represented in panels B and C were extracted from Canals et.al. [43]. (D) PBMC were infected at two different MOI (2 and 5) with STM-D23580 (blue), STM-4/74 (green) or STM-4/74 RibB ++ (pink).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The S. Typhimurium serovar causes two-thirds of iNTS in sub-Saharan Africa, and phylogenetic analysis has revealed that the bacteria represent a distinct pathovariant that is multidrug resistant and belongs to a specific multi-locus sequence type, S. Typhimurium Sequence Type 313 (ST313) [Kingsley et al, 2009;Okoro et al, 2012;Canals et al, 2019;Van Puyvelde et al, 2019]. Recent studies have addressed the abilities of the ST313 bacteria to disseminate systemically, as well as their capacity to survive intracellularly in various experimental models, including macrophages [Herrero-Fresno et al, 2014;Carden et al, 2015;Ramachandran et al, 2015;Singletary et al, 2016;Lacharme-Lora et al, 2019].…”
Section: Introductionmentioning
confidence: 99%